Clip Reconstruction of a Previously Leaked Large Complex Posterior Communicating Segment Aneurysm with Extradural Anterior Clinoidectomy - Baykal, Duygu; Ozaydin, Burak; Erginoglu, Ufuk; Baskaya, Mustafa K. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Fusiform or near-fusiform aneurysms that involve the long segment of the supraclinoid internal carotid artery (ICA) pose significant challenges to neurovascular surgeons. Involvement of the origin of vital branching arteries in this segment may preclude safe treatment with flow diverting stents. In addition, clip reconstruction may also not be possible in this region due to entire or near-entire involvement of the circumference of the ICA (Fig. 1). In this video article, we present a case of a complex and previously leaked, (visualized with hemosiderin) aneurysm of the posterior communicating segment of the ICA, in a 60-year-old female. Multiple complexities made this aneurysm challenging to treat. These included (1) a 270-degree encirclement of the ICA with multiple lobulations that left only a small section of nondiseased vessel wall, (2) a relatively short segment of the supraclinoidal ICA that made proximal control challenging thus requiring an extradural anterior clinoidectomy, (3) a fetal posterior communicating artery that originated immediately proximal to the beginning of the aneurysm, and lastly, (4) an anterior choroidal artery that was firmly adherent over the aneurysm dome. In this video, we present the microsurgical steps for dealing with this complex aneurysm, including extradural clinoidectomy and clip reconstruction (Fig. 2). Postoperatively, the patient woke up without any deficits. Angiography showed complete obliteration of the aneurysm.The link to the video can be found at: https://youtu.be/3Zz-ecvlDIc.
Keywords: complex aneurysm; hemosiderin; anterior clinoidectomy; fetal posterior communicating artery